INTERACTIVE ANIMATION VIDEO DEVELOPMENT BASED ON DISCOVERY LEARNING USING ADOBE CREATIVE CLOUD AND THE LEARNING MANAGEMENT SYSTEM MOODLE - Sitorus, Patar Ariyanto; Pujianto, Pujianto (Jurnal Pendidikan Matematika dan IPA, 2025)
This study aims to measure the feasibility of interactive animated videos based on discovery learning, assisted by Adobe CC and LMS Moodle, that have been developed. The method used in this study is research and development/(R&D) with a 4D development model. The 4D development model process carried out in this study includes the definition, design, and development stages; the dissemination stage was not carried out in this study. The feasibility of this product was validated by two material experts and two media experts who have a minimum educational background of a doctorate and a minimum of 3 years of teaching experience at the University, based on the validation results using a questionnaire, the following results were obtained: a total final score of 93.3% by material experts and a total final score of 100% by media experts. After receiving the validation results from experts, the next stage is to conduct a limited test with a sample of 12 students and two science teachers. Limited testing was carried out to determine the practicality and readability of the product being developed. Based on the limited test results, a total score of 97.5% was obtained for the practicality of the product by science teachers and 100% for the readability of the product by students. Based on the research results, it can be concluded that interactive animation videos based on discovery learning, assisted by Adobe CC and LMS Moodle, meet the requirements to be implemented at the dissemination stage. The urgency in this study is the lack of learning media in the form of interactive animation videos based on discovery learning on earthquake material. This implies that the developed media can be effectively integrated into science classes to enhance students' understanding of earthquake concepts. Furthermore, the development approach used can serve as a practical framework for educators and developers to develop similar products in other science topics.